Risiko Pembiayaan Pada Perbankan Syariah - Susilowati, Kartiningsih; Falikhatun, Falikhatun (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2023)
This study aims to examine the impact of financing growth, bank capital, and funding liquidity on financing risk. We also set bank size and GDP growth as control variables. The dummy variable is used as an influence on financing risk before and during the Covid-19 pandemic. Our data were analyzed using panel data regression analysis. Quantitative research in the form of Islamic banking financial reports in Southeast Asian and Middle Eastern countries for 2012-2021 was selected as our sample with a total of 260 observations. We found that, two of the three variables were significant. Financing Growth has a significant negative effect on Financing Risk, Bank Capital has no effect on Financing Risk, and Funding Liquidity has a significant negative effect on Financing Risk. Penelitian ini bertujuan untuk menguji dampak pertumbuhan pembiayaan, permodalan bank, dan likuiditas pendanaan terhadap risiko pembiayaan. Kami juga menetapkan ukuran bank dan pertumbuhan PDB sebagai variabel kontrol. Variabel dummy digunakan sebagai pengaruh risiko pembiayaan sebelum dan saat pandemi covid-19. Data kami dianalisis menggunakan analisis regresi data panel. Penelitian kuantitatif berupa laporan keuangan perbankan syariah di negara Asia Tenggara dan Timur Tengah tahun 2012-2021 dipilih sebagai sampel kami dengan total 260 observasi. Kami menemukan bahwa, dua dari tiga variabel signifikan. Pertumbuhan pembiayaan berpengaruh negatif signifikan terhadap risiko pembiayaan, modal bank tidak berpengaruh terhadap risiko pembiayaan, dan likuiditas pendanaan berpengaruh negatif signifikan terhadap risiko pembiayaan.